A diagnostic survey of infants referred for chromosome analysis in the neonatal period. Issue 6247 (18th October 1980) - Winter, R M; Ridler, M A; McKeown, J A
Abstract : Examination and assessment of 140 liveborn and stillborn infants referred within two weeks of birth for chromosome analysis showed that 48 had Down's syndrome, 12 other chromosome abnormalities, 17 single gene disorders, 18 recognisable anomalads, 8 recognisable syndromes of unknown aetiology, and the remainder were undiagnosed. Of the non-Down's cases that were diagnosed, 21% had a chromosomal abnormality. These results suggest that a request for chromosome analysis in the newborn period should be viewed as one step in syndrome identification.